Comprehensive Treatment of Patients with Dislocation of the Articular Disc of the Temporomandibular Joint with Different Types of Occlusal Splints - V. Chkhikvadze, Tina; M. Roschin, Evgenii; V. Bykovskaya, Tatiana; M. Gusarov, Artem; V. Ermolin, Dmitry; Yu. Ivanov, Sergey (International Journal of Psychosocial Rehabilitation, 2020)
The paper presents the results of treatment of patients with disc dislocation of the temporomandibular joint (TMJ) by using occlusion splints. At the initial stage, distraction splints were used, and at the second stage, when signs of reposition appeared, the distraction splints were modified to uncoupling splints by means of an increase in the number and area of occlusal contacts. In the manufacture of splints, two techniques were used: first, the classical method, when the gypsum splint model was formed using the mechanical face articulator; second, CAD/CAM technology. At the preliminary stage of treatment, all patients were diagnosed using the optical axiograph. The results of axiography were used for the manufacturing of distraction splints. Axiography was also carried out every three weeks at all the treatment stages. An algorithm of treatment was developed, which implies the treatment of patients with internal TMJ disorders caused by articular disc dislocation is based on the results of the optical axiography. Treatment monitoring and correction of occlusal splints are also carried out using optical axiography. In patients with articular disc dislocation, it is advisable to use distraction splints with their subsequent upgrade to uncoupling splints after signs of repositioning occur. The main purpose of using uncoupling splints at the second stage of treatment of the patients with dislocation of the articular disc is the stabilization of the new position of the lower jaw to expand the joint space. The study has not revealed differences in the effectiveness of treatment with distraction splints manufactured by various methods. In the absence of positive dynamics, a combination of conservative (uncoupling splints) and surgical (intra-articular injections, arthroscopy) treatment is recommended.